Image quality of two full field digital mammography using a female breast phantom - Kanaga Kumari Chelliah; Ang, Wee Chin; Abd Aziz Tajuddin; Shantini A. Arasaratnam; Suraya Aziz; Laila Suryani Elias (Penerbit UKM, 2009)
Digital mammography has been progressively introduced in screening centers and the concern is to achieve an image of diagnostic value which would be able to detect early changes in the breast tissue. The aim of this study was to evaluate the image quality of mammograms using quantitative and qualitative methods of two FFDM systems with variations in breast thickness and anode/ filter combination. This study was done from January to April 2008 with two FFDM systems; Siemens Mammomat NovationDR at Diagnostic Imaging Department, Hospital Kuala Lumpur and Hologic Lorad Selenia at Breast Clinic, National Cancer Society. A CIRS012A tissue equivalent breast phantom (4, 5 and 6 cm) thickness was used to obtain images in the craniocaudal plane with 26-32 kVp and a combination of molybdenum/molybdenum (Mo/Mo) and molybdenum/rhodium (Mo/Rh) anode/filter. For the qualitative evaluation, two independent radiologist with a minimum of five years experience was used to score the images. Wilcoxon Sign Rank Test showed that there are no significant differences (p > 0.05) in image quality between both the FFDM systems. Kappa analysis had a poor agreement between the scores given by the two radiologists. The quantitative analysis using Mann-Whitney test showed that there are significant differences (p < 0.05) between the SNR values of both FFDM systems. Although the qualitative evaluation was similar, the study showed that Lorad Selenia had a significantly superior SNR value, hence would be a better tool to detect early changes in the breast tissue. This study also demonstrated that a lower kVp is more suitable with molybdenum filter and as the breast thickness is increased rhodium filter with higher kVp displayed better quality images.